2021
DOI: 10.3917/rpsf.141.0031
|View full text |Cite
|
Sign up to set email alerts
|

Habiter en Ehpad au temps de la Covid-19

Abstract: Caisse nationale d'allocations familiales | « Revue des politiques sociales et familiales » 2021/4 n°141 | pages 31 à 48

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 11 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Consequently, it has been suggested that decision-making processes related to housing need to be reconsidered, taking into account the pandemic's impact (Haghighi, 2021). Research conducted during COVID-19 lockdowns has revealed that the pandemic has adversely affected the lives of older adults in EPHAD 4 and mothers overwhelmed with housework (Balard et al, 2021;Lambert et al, 2021). Furthermore, individuals who previously had limited socialisation opportunities, such as those living in EPHAD or mental health institutions, have experienced increased con nement due to the pandemic, exacerbating existing problems (Messy, 2020;Sordes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it has been suggested that decision-making processes related to housing need to be reconsidered, taking into account the pandemic's impact (Haghighi, 2021). Research conducted during COVID-19 lockdowns has revealed that the pandemic has adversely affected the lives of older adults in EPHAD 4 and mothers overwhelmed with housework (Balard et al, 2021;Lambert et al, 2021). Furthermore, individuals who previously had limited socialisation opportunities, such as those living in EPHAD or mental health institutions, have experienced increased con nement due to the pandemic, exacerbating existing problems (Messy, 2020;Sordes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%